Circumstantial risk factors for death after intensive care unit-to-unit inter-hospital transfer—a Swedish registry study - Jesper Sternley; Karl Stattin; Max Petzold; Jonatan Oras; Christian Rylander (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Unit-to-unit transfer of critically ill patients infers hazards that may cause adverse events. Circumstantial factors associated with mortality after intensive care include days in the ICU, night-time or weekend discharge and capacity transfer as compared to other reasons for transfer. Distance travelled may also constitute an indirect risk. The aim of this study was to assess potential associations between these circumstantial factors and the risk of death 30 days after transfer. Methods Data from 2015 to 2019 was retrieved from the Swedish Intensive Care Registry. Logistic regression was used for risk analysis. Results Among 4,327 patients, 965 (22%) were deceased 30 days after transfer. 1351 patients undergoing capacity transfer had a higher morbidity than patients transferred for other reasons. Using univariable logistic regression, days spent in the referring ICU before transfer, capacity transfer as compared to clinical transfer and repatriation as well as SAPS3 in the receiving ICU were associated with a higher risk of death at 30 days. However, after multivariable regression with adjustment for ICD-10 diagnosis and Standardised Mortality Rate in the receiving ICU, these associations were lost. Conclusion Our results suggest that inter-hospital transfer is safe to carry out at any time of day and over shorter as well as longer distances.